Analysis of Water Discharge and Draining Time for Pump Types in Ship Leakage Draining Systems - Ratna Mustika Yasi; Charis Fathul Hadi; Ananta, Viky (Fakultas Teknik Universitas PGRI Banyuwangi, 2024)
Ship accidents due to cracks and leaks in the ship's hull are closely related to the flow of water entering the ship's hull. A ship's pump system plays an important role in removing water from a ship, but pump failure can result in the accumulated water not being able to be drained immediately which can result in increased water pressure and the potential sinking of the ship. This research used a trial method with a fiberglass ship prototype that was provided with a 3mm leak hole, using four different types of pumps and testing was carried out in a water-filled tub. Based on the results of the research carried out, it can be concluded that the water discharge of pumps 1, 2, 3 and 4 respectively is 0.0000261, 0.0000251,: 0.0000326, and 0.0000566 liters/second. The power of pump 4 is more effective in draining water volume resulting in less draining time compared to the other three pumps .